The limits of satire in Rameau’s Nephew, by Denis Diderot - Garroux, Daniel Santos (Revista de Letras, 2019)
This article seeks to establish a relation between the poetics of Rameau’s Nephew and the satire genre. The hypothesis is that the text, by modifying some criteria of representation, breaks with the prevailing conventions of the genre during its time. We do not intend, though, to take, as a parameter, satire in abstractu, but to explore some uses and conceptions of this genre that are proper to the second half of the Eighteenth century, which will not be discussed exhaustively. We aim at bringing to the discussion some hegemonic and recurrent traits, in order to highlight the aspects that are similar to what we find in Diderot’s text.